Three challenges for China's outward FDI policy - Karl P. Sauvant (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
China faces three main challenges: in the short-term, dealing with the growing skepticism with which its FDI is perceived in some host countries; in the medium-term, responding to efforts to discipline the use of home country measures; in the long-term, contributing to the establishment of a multilateral framework for investment.
Keywords: 330